Reducing dandori processing time using the single minute exchange of die method in swaging areas in automotive rubber components company - Sudarmaji, Heri; Setiawan, Rohmat; Adhika, Muhammad; Pamungkas, M.Dimas Satria (Universitas Mercu Buana, 2023)
The automotive component company is engaged in the manufacture of automotive rubber components. Based on data obtained from field observations, it was found that the Dandori process on the swaging Nox machine, especially TA090 type, had the highest downtime compared to another component. Based on these problems, research uses the Single Minute Exchange of Die (SMED) method to reduce Dandori downtime in the TA090 swaging process. The SMED method was carried out in three stages: 1. identify internal and external setup, 2. Converting internal to external setup, and 3. Streamlining aspects of operation. In addition, it also used data processing tools, namely SMART, fishbone, and 5W+1H as support to solve this problem. Improvements were made by converting internal work elements into external ones and streamlining aspects of operation by improving on man, method, and machine/tools categories. The result of these improvements was a decrease in downtime of 39 minutes 48 seconds and the improvement efficiency achieved was 81.2%.